2020
DOI: 10.1021/acs.jchemed.0c00254
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Active Learning Combination Reveals Better Performance on Cognitively Demanding General Chemistry Concepts than Active Learning Alone

Abstract: Benefits of metacognition and active learning on student performance are well understood; however, little is known about the effect of the "explicit teaching of metacognition" combined with active learning on student performance in chemistry courses. Using a quasi-experimental study design, we investigated: (1) differences in performance in the General Chemistry I course between students exposed to the explicit teaching of metacognition combined with active learning (treatment group) and their counterparts who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 41 publications
1
47
1
1
Order By: Relevance
“…Overall, results from the current study indicate that the muddiest points have the potential to level the playing field in general chemistry courses toward providing equitable participation and access to learning. Muddiest point activities enhance metacognitive regulation skills by encouraging students to reflect and monitor their learning progress (Mutambuki et al, 2020;Muteti et al, 2021). In the light of the current results, we contend that instructor pre-chosen assessment prompts, such as structured-clicker questions, quizzes, homework, among others, can overlook potential learning blind spots that students may be struggling with, yet not realized in real-time.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Overall, results from the current study indicate that the muddiest points have the potential to level the playing field in general chemistry courses toward providing equitable participation and access to learning. Muddiest point activities enhance metacognitive regulation skills by encouraging students to reflect and monitor their learning progress (Mutambuki et al, 2020;Muteti et al, 2021). In the light of the current results, we contend that instructor pre-chosen assessment prompts, such as structured-clicker questions, quizzes, homework, among others, can overlook potential learning blind spots that students may be struggling with, yet not realized in real-time.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, Muteti et al found that most students enrolled in the introductory general chemistry course mainly employed rote memorization, with reflective learning reported by a handful of the study participants (Muteti et al, 2021). Muddiest point activities enhance metacognitive regulation skills by encouraging students to reflect and monitor their learning progress (Mutambuki et al, 2020;Muteti et al, 2021). Therefore, it is likely that introducing the muddiest point activities early in the semester leveled the playing field for the vulnerable students, that is, minority and minority, first-generation students, to master the concepts and attain better scores.…”
Section: Discussionmentioning
confidence: 96%
“…There is a growing body of literature investigating the impact of teaching metacognitive strategies, sometimes in conjunction with other pedagogical practices. Examples include Cook et al (2013), Kaldor andSwanson (2018, 2019), Swanson et al (2021), Muteti et al (2021, Mutambuki et al (2020), andBenko et al (2019). A university student who used metacognition to improve academic performance recently published an account of her experience (Chen, 2020).…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Later lectures included worked problems and opportunities for guided practice with feedback . Metacognition, the awareness of a learner’s thinking process, improves problem solving and learning in general. Throughout the course, students filled out worksheets to support metacognition, in an approach similar to Yuriev et al Students predicted their ability to solve a problem; , identified the known and unknown information and the connection between the two; provided work to solve the problem; described methods to check their work; and described any connections to other problems they could discern. Students completed some worksheets in-class for practice (with no grade) and a few for homework (for a grade), and answers were posted on Moodle.…”
Section: Initial Formatmentioning
confidence: 99%